Survey of Lay-Up Skill Levels Among Basketball Extracurricular Students at SMP Negeri 17 Kota Bengkulu - Gayane Vatona; Nurian Aprilia Windasari; Zacky Zell Vano; Muhammad Royhan; Aldi Prasetyo; Martiani Martiani (Educative Sportive, 2025)
This study aims to describe and map the lay-up skill levels of students in the basketball extracurricular program at SMP Negeri 17 Bengkulu City. This was a descriptive quantitative study using a survey method. The population and sample consisted of all 25 active basketball extracurricular students, selected using total sampling. The research instrument utilized a lay-up skill test consisting of 10 attempts (5 from the right side and 5 from the left side). The data were analyzed using descriptive percentage statistics. The results indicated that the students' lay-up skills fell into the "Medium" category at 40% (10 students). Meanwhile, the "Good" category was 24% (6 students), "Poor" was 20% (5 students), "Very Good" was 8% (2 students), and "Very Poor" was 8% (2 students). On average, the students achieved a score of 5.44 or 54.4%. The study concludes that the lay-up skills of students at SMP Negeri 17 Bengkulu City still require improvement, particularly in footwork synchronization and ball release coordination. Coaches are advised to optimize basic footwork drills and ambidexterity training to enhance student performance.